Synthesis of a New Zn2+/Fe3+ Octa(aminopropyl)silsesquioxane Complex and Its Voltammetric Behavior Towards N-acetylcysteine - do Carmo, Devaney Ribeiro [UNESP]; Peixoto, Murilo Santos [UNESP]; dos Santos Felipe, Alexsandro [UNESP]; Sales, Abner Santos Baroni [UNESP]; Filho, Newton Luiz Dias [UNESP]; de Souza Magossi, Mariana [UNESP] (Springer Nature, 2022)
A zinc-modified octa(aminopropyl)silsesquioxane and the cyan compound Na2[Fe(CN)5NO] were prepared to create a hybrid electroactive material (ACZnN) characterized employing the spectroscopic techniques Raman spectroscopy, Diffuse Reflectance (DR), X-Ray diffraction (XRD), Scanning Electronic Microscopy (SEM), thermogravimetric analysis (TGA) and voltammetric measurements. The cyclic voltammetry technique indicated the solid ACZnN on the electrode surface as presenting two redox processes, with EIθ' = 0.21 V and EIIθ' = 0.51 V (vs Ag/AgCl(sat)) attributed to the redox pair Fe2+(CN)5NO/ Fe3+(CN)5NO in the absence and presence of Zn2+, respectively, as well as adequate stability, reliability and efficiency for practical applications. The ACZnN-modified graphite paste electrode exhibited a sensitive and catalytic oxidation response towards N-acetylcysteine and was successfully employed 1in the catalytic electro-oxidation of N-acetylcysteine employing differential pulse voltammetry techniques. The lowest limit of detection and best amperometric sensitivity obtained by differential pulse voltammetry were 0.657 µmol L−1 and 500 mA/mol L−1, respectively, from 1.0 × 10–6 to 1.0 × 10–5 M. Further analyses applying this method also demonstrated the compound’s efficiency in detecting N-acetylcysteine in synthetic urine samples.
Keywords: N-acetylcysteine; Sensor; Silsesquioxane; Spectroscopy; Voltammetry